The challenges of disabled entrepreneurs: a systematic review / Norliza Saiful Bahry ... [et al.] - Saiful Bahry, Norliza; Kori, Nur Liana; Mohd Ali, Ainnunazlee; Mat, Azmi; Adzmi, Azian (Universiti Teknologi Mara, Selangor: Puncak Alam Campus: Faculty of Business and Management, 2023)
The motivations of disabled individuals to become entrepreneurs can be influenced by various factors. Throughout their careers and projects, entrepreneurs with disabilities may face multiple personal, social, and political obstacles. This research aims to develop a rigorous, systematic examination of the literature on the obstacles disabled people must overcome to become entrepreneurs. The literature review focused on analyzing ten articles from Web of Science and Scopus. The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) is used to organize the field of research. This compilation of peer-reviewed research papers is necessary for academia and government to realize the vision of shared prosperity by 2030.